Effect of Yava Syamaka Peya and Suryanamaskara in Overweight Adults - V Greeshma; Jyothi R; A. Nafeesath Beevi (International Journal of Ayurveda and Pharma Research, 2025)
Overweight refers to abnormal or excessive fat accumulation that presents a risk to health. Overweight is currently widespread in both developed and developing countries, affecting both children and adults. A higher prevalence is observed among individuals of high socioeconomic status, particularly in urban areas. Modern lifestyles and poor dietary habits are the primary factors contributing to the development of overweight. If not managed promptly, overweight can progress to obesity, leading to a host of pathological complications. The management of overweight should focus on promoting appropriate dietary choices and boosting energy expenditure through physical activity. Yava Syamaka Peya mentioned in Bhavaprakasha Nighantu was adopted as a dietary intervention. Along with this diet, Suryanamaskara was made into the daily routine of participants for a period of 3 months. The intervention, consisting of 300ml of Yava Syamaka peya along with the daily practice of 12 rounds of Suryanamaskara, was conducted in 31 subjects. The results were analysed using the paired t-test and repeated measures ANOVA test. The study found a considerable reduction in body weight, with an average loss of 6.65 kg over 3 months. Participants experienced an average decrease of 2.645 kg/m² in BMI and a reduction of 0.035 in the waist-hip ratio. Additionally, FBS decreased by 14.71 mg/dl, and total cholesterol levels dropped by an average of 23.42 mg/dl. These results were statistically significant. From this, it is concluded that the intake of Yava Syamaka peya along with the practice of Suryanamaskara for 3 months is effective in reducing overweight.